2019
DOI: 10.1002/clen.201800452
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Vegetation Carbon, Nitrogen, and C/N Ratio in a Tamarix chinensis Coastal Wetland of China

Abstract: Variations in carbon (C) and nitrogen (N) of the vegetation in aTamarix chinensis coastal wetland located in Laizhou Bay, China, are analyzed. It is found that T. chinensis accumulates more C and N than the surrounding herbs, and it allocates more C and N in the aboveground parts but less in the roots. Branches store more C, whereas leaves and flowers accumulate more N than other tissues. The C and N contents in the aboveground parts of T. chinensis are mainly influenced by pH, electrical conductivity (EC), wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…The C, N, and P contents of plants are affected by the comprehensive effects of environmental factors, such as the soil physical and chemical properties and the atmospheric carbon dioxide concentration [ 48 ]. In this study, RDA analyses were used to evaluate the key environmental factors that affect the stoichiometric characteristics of leaf C, N, and P. Soil is the main source of plant nutrients [ 49 , 50 ]; therefore, the soil C, N, and P concentrations are expected to determine the concentrations of plant C, N, and P. In addition, our study revealed that soil salinity and soil C/N ratio greatly impacted the eco-stoichiometric characteristics of S. alterniflora leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C, N, and P contents of plants are affected by the comprehensive effects of environmental factors, such as the soil physical and chemical properties and the atmospheric carbon dioxide concentration [ 48 ]. In this study, RDA analyses were used to evaluate the key environmental factors that affect the stoichiometric characteristics of leaf C, N, and P. Soil is the main source of plant nutrients [ 49 , 50 ]; therefore, the soil C, N, and P concentrations are expected to determine the concentrations of plant C, N, and P. In addition, our study revealed that soil salinity and soil C/N ratio greatly impacted the eco-stoichiometric characteristics of S. alterniflora leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that a low C/N ratio can promote microbial decomposition and N mineralization, while a high C/N ratio can slow down the mineralization of organic matter and organic N and promote the fixation of organic C [ 51 ]. In addition, high salinity levels can also slow down the mineralization of organic C [ 48 , 52 ]. A significant correlation was detected between the soil organic C and the leaf C, N, and P levels ( p < 0.01, Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This species is found in the western of USA, where it is considered as an invasive species (Swaminathan et al, 2020;Xie et al, 2020). In China, T. chinensis is the vital part of the coastal wetland ecological restoration projects of "Southern Mangrove and Northern Tamarisk" and "Blue Carbon" (Xie et al, 2019;Yang et al, 2021). As one of the dominant shrub in northern China, T. chinensis contributes largely to shoreline protection, carbon sequestration, and ecological function (Jiao et al, 2021;Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%